Challenges in the Diagnosis and Management of Autoimmune Hepatitis - Albert J Czaja (Canadian Journal of Gastroenterology)
BACKGROUND: Autoimmune hepatitis has diverse clinical phenotypes and outcomes that challenge current diagnostic criteria and management algorithms.